Investment and enterprise responsibility review : analysis of investor and enterprise policies on corporate social responsibility (UN New YorkUS, 2011)
Provides an analysis of the voluntary practices of TNCs and large institutional investors as these institutions respond to issues of corporate social responsibility.
Keywords: TRANSNATIONAL CORPORATIONS